2023
DOI: 10.1007/s10311-023-01603-4
|View full text |Cite
|
Sign up to set email alerts
|

Methods to prepare biosorbents and magnetic sorbents for water treatment: a review

Abstract: Access to drinkable water is becoming more and more challenging due to worldwide pollution and the cost of water treatments. Water and wastewater treatment by adsorption on solid materials is usually cheap and effective in removing contaminants, yet classical adsorbents are not sustainable because they are derived from fossil fuels, and they can induce secondary pollution. Therefore, biological sorbents made of modern biomass are increasingly studied as promising alternatives. Indeed, such biosorbents utilize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(27 citation statements)
references
References 549 publications
0
27
0
Order By: Relevance
“…58 These include microbial biomass, agricultural wastes, nano-MgO, Fe 3 O 4 nanoparticles, CaO/Fe 3 O 4 nanoparticles, and activated carbon/Fe 3 O 4 nanocomposites, which is a composite of nanoadsorbents and biosorbents. 59 5.4. Nanobiosurfactants.…”
Section: Mechanism Of Nanotechnology: Reduction Reaction Immobilizati...mentioning
confidence: 99%
“…58 These include microbial biomass, agricultural wastes, nano-MgO, Fe 3 O 4 nanoparticles, CaO/Fe 3 O 4 nanoparticles, and activated carbon/Fe 3 O 4 nanocomposites, which is a composite of nanoadsorbents and biosorbents. 59 5.4. Nanobiosurfactants.…”
Section: Mechanism Of Nanotechnology: Reduction Reaction Immobilizati...mentioning
confidence: 99%
“…Moreover, the adsorption capacity and efficiency are major concerns for the adsorbents. Metal leaching as well as the toxicity of metal-based adsorbents like metal oxides and magnetic adsorbents is a further major cause of concern. Nowadays, metal-free systems such as heteroatom-enriched adsorbents are gaining more attention. Recently, various heteroatom-enriched materials for the removal of Pb 2+ from aqueous solutions have been discovered. Owing to the tunable textural features, high specific surface area, and heteroatom enrichment, heavy metal ions are selectively removed from aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Many adsorbents have been reported to remove Pb 2+ from aqueous solutions such as metals, metal oxides, resins, activated carbon, metal–organic framework, zeolites, and biochar-based adsorbents. There are several natural adsorbents, such as biological waste material like low-value lignocellulose, used to synthesize activated carbon having a specific surface area of 1368 m 2 g –1 , as well as the carbon nanotube for wastewater treatment for the removal of lead ions from aqueous solution. Although these types of adsorbents have been synthesized by a green method and natural waste, they lack selectivity. Moreover, the adsorption capacity and efficiency are major concerns for the adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the best method is the adsorption process, which is due to its unique properties in terms of reducing time and obtaining a high removal rate of metal ions and radioactive isotopes using different adsorbents. [5][6][7][8][9][10] Lately, biomass materials like coconut shell activated carbon, 11,12 sawdust, [13][14][15] activated carbon, [16][17][18][19] natural materials, 20,21 activated carbon derived from pine sawdust, 22 magnetic plastic waste-biomass char composite (MPBC), 23 activated carbon and carbon nanotubes that synthesized from biomass, [24][25][26][27][28][29] .....etc., have been used as adsorbents to isolate heavy metal ions, organics, dyes and radioactive isotopes from contaminated water. Where, these biomass materials include numerous function groups as -COOH, -OH, and CO and these groups are associated with the element through ion-exchange, van der Waals interactions, complexation or co-precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the extraction and separation of cerium(III) using a modified graphite adsorbent, 53 adsorption of Ce(III) onto cellulose/graphene composite, 54,55 capture of cerium(III) using a ligand, 56 adsorption of Ce 3+ ions by a hydrophobic ionic liquid, 57 capture of Sr 2+ ions by a layered potassium neodymium phosphate, 58 removal of Sr 2+ ions by potassium phosphatoantimonate, 59 performance of membranes for the separation of Sr 2+ ions, 60,61 separation of strontium by resin, 62 layered potassium calcium phosphate for Sr(II) removal, 63 selective Sr 2+ uptake by oxalates, 64 adsorption of strontium ions by a metal-organic framework, 65 adsorption of Sr(II) in acid solution by a porous silica, 66 and adsorption of strontium radionuclide onto zeolites. 9 Newly, many researches have focused on the removal of contaminants from polluted water using the adsorption process in the presence of ultrasound waves, which greatly helps the transfer and entry of the adsorbate ions into the pores of the absorbent material. [67][68][69][70][71][72][73] Among them, Sivalingam et al indicated that the adsorption method in the presence of ultrasonication reduces the time for the adsorption process to occur.…”
Section: Introductionmentioning
confidence: 99%